What Should Be the Data Sharing Policy of Cognitive Science?. (17th January 2013) - Pitt, Mark A.; Tang, Yun
Abstract There is a growing chorus of voices in the scientific community calling for greater openness in the sharing of raw data that lead to a publication. In this commentary, we discuss the merits of sharing, common concerns that are raised, and practical issues that arise in developing a sharing policy. We suggest that the cognitive science community discuss the topic and establish a data‐sharing policy.